The work in professional and technological education and the historical-cultural theory (Research, Society and Development, 2022)
The goal of this study is to analyze the concept of work in Professional and Technological Education (PTE), specifically after the creation of the Federal Institutes (FIs), relating it with the Historical-Cultural Theory developed by Vygotsky. Discussions of the main concepts developed by Vygotsky will be made, such as mediation, Zone of Proximal Development (ZPD) and Internalization, aiming at verifying how this theory can contribute to Brazilian PTE. We shall also make a brief assessment of the two theoretical approaches to vygotskyan thought: the Theory of Activity and the Communities of Practices. It is a bibliographic research with qualitative approach. On reflecting over Vygotsky’s contributions for professional education, it is necessary to think of an education in which man is a historical and cultural being and an agent for transformation of the environment in which he survives. His studies show the importance of mediated work, with the prevalence of interaction and the appreciation of the experiences of both teacher and student. In this way, his theory contemplates the professional formation with the goal of emancipation.